Gambaran Serum Ureum, dan Kreatinin pada Tikus Putih yang diberi Fraksi Etil Asetat Daun Alpukat (THE PROFIL OF SERUM, UREUM AND CREATININE OF AETHYL ACETATE FRACTION AVOCADO LEAVES IN WHITE RATS) - Wientarsih, Ietje; Madyastuti, Rini; Prasetyo, Bayu Febran; Firnanda, Dian (Jurnal Veteriner, 2012)
Nephrolithiasis is one of urologic disease due to crystallization urine in urinary system. Traditionally,avocado leaves has long been used for the treatment of nephrolithiasis because flavonoid in this plant canfacilitate the watering of crushing stone in the urinary tract. The aims of this study was to determine theeffect of aethyl acetate fraction of avocado leaves on ureum and creatinine level. Twenty white male rats(Sprague dawley, weight 200-300g) were divided into four groups. Normal control group (A) was givenaquadest ad libitum. Negative control group (B) and treatments group (C and D) were given ethyleneglycol 0.75% and ammonium chloride 2% to induce the formation of calcium oxalate crystal. Group C andD were given aethyl acetate fraction with different levels (100mg/kg bb and 300mg/kg bb for fourteen days).Blood samples were taken before and after treatment. The result showed that aethyl acetate fractioncould not decrease serum blood level of ureum and creatinine. Serum blood level ureum and creatinine ingroup D increased significantly compared to group A, B, C after fourteen days treatment. The used ofethylene glycol caused acute tubular necrosis. It therefore appears that ethyl acetate solvent was not ableto extract flavonoids to prevent renal dysfunction.
Keywords: aethyl acetate, fraction, calcium oxalate, ureum, creatinine